EFEKTIVITAS KONSUMSI EKSTRAK DAUN KELOR TERHADAP PENINGKATAN PRODUKSI ASI IBU NIFAS DI PMB ROSITA KOTA PEKANBARU - Anisca Pratiwi Elpardia; Rika Ruspita; Rifa Yanti; Nurhidaya Fitria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Exclusive breastfeeding is often constrained by low lactation volume among postpartum mothers, necessitating the use of locally available interventions to support successful breastfeeding. Moringa oleifera leaves are known to contain phytoestrogens, vitamins, and minerals that play a role in stimulating breast milk production. This study aimed to analyze the effectiveness of Moringa oleifera leaf extract in increasing breast milk production among postpartum mothers at PMB Rosita, Pekanbaru. This research employed a pre-experimental design with a pretest-posttest approach. A total of 12 postpartum mothers were selected as respondents. Breast milk production was measured before and after the administration of Moringa oleifera extract, and data were analyzed using a independent sample t-test. The results revealed that before the intervention, the mean breast milk production was 53.33 with a standard deviation of 17.23, and most respondents (66.7%) showed no increase. After the intervention, the mean production rose to 74.17 with a standard deviation of 19.28, with almost all respondents (91.7%) experiencing an increase. Statistical analysis showed a p-value of 0.002 (p0.05), indicating a significant difference between pretest and posttest. In conclusion, Moringa oleifera leaf extract was proven effective in enhancing breast milk production among postpartum mothers. These findings support lactation physiology theory and strengthen recent literature on the use of local plants as natural galactagogues. The intervention has the potential to serve as a complementary strategy to promote exclusive breastfeeding and improve maternal and infant health in Indonesia.Keyword : Moringa oleifera, Breast milk production, Postpartum mothers, Natural, Galactagogue